2001
DOI: 10.1016/s0040-6090(00)01615-1
|View full text |Cite
|
Sign up to set email alerts
|

Thin silicon films ranging from amorphous to nanocrystalline obtained by hot-wire CVD

Abstract: In this paper we present results on silicon thin films deposited by Hot-Wire CVD at low substrate temperature (200ºC). Films ranging from amorphous to nanocrystalline were obtained by varying the filament temperature from 1500 to 1800ºC. A crystalline fraction of 50% was obtained for the sample deposited at 1700ºC. The results obtained seemed to indicate that atomic hydrogen plays a leading role in the obtention of nanocrystalline silicon. The optoelectronic properties of the amorphous material obtained in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…14 and 15 are microcrystallized. As HW is heated, the deposition rate increases with increasing HW temperature except for the case investigated by Soler et al 17) which shows the saturation of the deposition rate independent of the HW temperature. It is reported that the decomposition efficiency of SiH 4 increases with increasing HW temperature and approaches 1 at around 2100 C 20) Thus, the deposition rate increases when the HW temperature is high and the supply of SiH 4 is not depleted.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…14 and 15 are microcrystallized. As HW is heated, the deposition rate increases with increasing HW temperature except for the case investigated by Soler et al 17) which shows the saturation of the deposition rate independent of the HW temperature. It is reported that the decomposition efficiency of SiH 4 increases with increasing HW temperature and approaches 1 at around 2100 C 20) Thus, the deposition rate increases when the HW temperature is high and the supply of SiH 4 is not depleted.…”
Section: Resultsmentioning
confidence: 84%
“…We also show the deposition rates in the same figure for films prepared by ECRCVD and HWCVD in the literature. 14,15,[17][18][19] It is well known that many parameters can affect the deposition rate, such as the dilution ratio of H 2 to SiH 4 , the gas pressure, the substrate temperature, the microwave power (ECR) and the HW temperature (HW). Hence, care is needed in comparing these data.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from annealing the samples after deposition, crystallinity can be induced in the layer during the deposition process either by control of the substrate temperature [14], by the control of the filament catalyzer [15], by increase of the hydrogen dilution ratio in the silane gas at constant deposition pressure or by the increase of the deposition pressure keeping constant the hydrogen dilution ratio in silane. As the first two processes happen at very high temperature of the substrate and/or the filament, they are thus are energy intensive; the last two processes are more attractive as they occur at low temperature of the substrate, sometimes without any heating of the substrate needed.…”
Section: Current Application Of Polymers and Nano Materialsmentioning
confidence: 99%